The Determination of Aspartame Levels and The Study of its Stability in some Locally Marketed Soft Drinks using High Performance Liquid Chromatography HPLC - ياسين, مفيد; الخليل, ديانا (Latakia University Journal -Medical Sciences Series, 2020)
In this research, levels of aspartame in locally marketed soft drinks were determined using high performance liquid chromatography - reverse phase (RP-HPLC). The stability of aspartame in these drinks was then evaluated under the conditions of preservation and storage during (one month, three months). The levels of aspartame in locally manufactured soft drinks ranged between (11.644-15.184) mg / 100 ml, while the levels in imported soft drinks were between (6.379-7.065) mg / 100 ml. By studying the effect of preservation and storage conditions, a significant decrease in aspartame levels was observed, this decrease ranged between (9.20% -19.79%) during the first month, and after three months the decrease was between (20.29% -40.16%).